TECHNOLOGICAL MONITORING OF ELECTRICAL RESISTANCE OF PRESSED CABLE CONDUCTORS IN PRODUCTION CONDITIONS - Y. A. Antonets (National Technical University "Kharkiv Polytechnic Institute", 2019)
This paper presents results of control of electrical resistance R production pressed aluminum cable conductors. Control of electrical resistance in manufacturing of cable production is the most massive non-destructive test, which provides a compromise between the manufacturer's costs for a high-conductivity material on the one hand and the user's operating costs from conducting heating losses on the other. For the adoption of technological solutions for the use of hot compression of solid aluminum wires (instead of cold drawing technology) for a specific size, a reliable determination of the probability of unacceptable values of electrical resistance R > Ř (probability of claims) in large masses of products is necessary. The application of statistical analysis of measurement results using the mathematical apparatus of boundary distributions is considered. In this case, the subject matter of the analysis is the distribution of the limit values of the control parameter, which makes it possible to reliably estimate the likelihood of the appearance of inadmissible values (probability of claims). An algorithm for determining the probability of the appearance of impermissible values of the electrical resistance R > Ř (probability of claims) for solid aluminum wires of low and medium voltage cables in the range of the cross-sectional area (120...240) mm2 based on the analysis of the results of control of the electrical resistance during a long technological period (18 months) manufacturing in production conditions. The use of the appeal potential of the technological solution as the cost of products, for which R > Ř is used, is proposed. The comparison of the appeal potential of the technology of hot pressing of solid aluminum and the technology of cold drawing (dragging) provided the same level of specific electrical conductivity of the metal is achieved.